SWOT-Analysis as a Tool to Achieve a State of Personal Well-Being; The European Proceedings of Social & Behavioural Sciences (EpSBS); Vol. 19 : Lifelong Wellbeing in the World (WELLSO 2016) - Pluchevckaya E. V. Emiliya Valerievna (2017, 2017)
Title screen